2014
DOI: 10.2478/pjvs-2014-0071
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of flunixin meglumine and meloxicam influence on postoperative and oxidative stress in ovariohysterectomized bitches

Abstract: The aim of this study was to compare the effect of flunixin meglumine (FM) and meloxicam (M) on postoperative and oxidative stress in ovariohysterectomized bitches. Twenty four bitches were divided into three groups (n=8 in each) and treated during premedication as follows: FM (2.2 mg/kg, iv, Fluvil, Vilsan, Turkey), M (0.2 mg/kg, sc, Maxicam, Sanovel, Turkey) or 0.9% saline (1 ml, iv, IE, Turkey) -control (C) group. The concentrations of serum cortisol, nitric oxide (NO), malondialdehyde (MDA), antioxidant po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
(39 reference statements)
4
16
0
Order By: Relevance
“…Our results show that plasma cortisol levels in the treatment groups were significantly lower than in the control group at 0-6 h as well as at 12 h post-extubation (Figure 3). One previous study demonstrated that ovariohysterectomy is a noxious stimulus in dogs, causing marked elevations in plasma cortisol for 6-12 h (Hansen et al 1997), and other studies have shown that post-operative cortisol levels were higher in dogs when meloxicam was used (Tsai et al 2013;Yilmaz et al 2014). All these results were consistent with our data.…”
Section: Discussionsupporting
confidence: 93%
“…Our results show that plasma cortisol levels in the treatment groups were significantly lower than in the control group at 0-6 h as well as at 12 h post-extubation (Figure 3). One previous study demonstrated that ovariohysterectomy is a noxious stimulus in dogs, causing marked elevations in plasma cortisol for 6-12 h (Hansen et al 1997), and other studies have shown that post-operative cortisol levels were higher in dogs when meloxicam was used (Tsai et al 2013;Yilmaz et al 2014). All these results were consistent with our data.…”
Section: Discussionsupporting
confidence: 93%
“…Clearly, BP has rapidly decreased the concentration of cortisol which reaches its level 30 minutes after the end of surgery [16]. The present study showed that cortisol levels were elevated in all groups and this finding was consistent with other reports [9,16,31]. On the other hand, the concentrations of cortisol rapidly decreased in BP and LP groups with respect to the control group.…”
Section: Discussionsupporting
confidence: 92%
“…Environmental changes, anaesthesia and surgical procedures comprise a response originated from the hypothalamic -pituitary -adrenal axis and the most important indicators of surgical stress are the changes in the blood levels of the cortisol hormone [11,12,29]. Devitt et al [9] reported that levels of cortisol increased until 2 h after standard or laparoscopic OHE in bitches, whereas Yilmaz et al [31] stated that the increment of the concentrations of cortisol was observed for 2.5 h in dogs following standard OHE. Clearly, BP has rapidly decreased the concentration of cortisol which reaches its level 30 minutes after the end of surgery [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FM, a nicotinic acid derivative, inhibits COX, which transfers arachidonic acid to prostanoids (Donalisio et al, 2013;Lee & Maxwell, 2014;Milovanović, Vučković, Prostran, Trailović, & Jovanović, 2016;Yilmaz et al, 2014). In China, FM has been used in cattle (Cetin et al, 2014;Cooke, Cappellozza, Guarnieri, & Bohnert, 2013;Currah, Hendrick, & Stookey, 2009;Huber, Arnholdt, Mostl, Gelfert, & Drillich, 2013;Newby et al, 2017), pigs (Whalin, Pairis-Garcia, Proudfoot, Stalder, & Johnson, 2016), horses (Duz, Parkin, Cullander, & Marshall, 2015;Keegan, Messer, Reed, Wilson, & Kramer, 2008), cats, dogs, and sheep (Marini et al, 2016;Paull, Lee, Colditz, Atkinson, & Fisher, 2007) to treat acute inflammation (Yang et al, 2013), musculoskeletal diseases, bellyache, pain, sow endometritis, mastitis, agalactia syndrome, and canine endotoxemia.…”
Section: Introductionmentioning
confidence: 99%